Dielectric properties and relaxation behaviors of Ba doped Sr0.97Sm0.02TiO3 ceramics in different sintering atmospheres. Issue 15 (15th November 2016) - Li, Guangyao; Liu, Hanxing; Hao, Hua; Liu, Jiajia; Chen, Zhuo; Huang, Xindi; Cao, Minghe; Yao, Zhonghua
Abstract: The Bax Sr0.97−x Sm0.02 TiO3 (x=0–0.4) ceramics in different sintering atmosphere were prepared by conventional solid-state reaction methods. The effect of different atmosphere on the dielectric properties of Bax Sr0.97−x Sm0.02 TiO3 ceramics was investigated. The giant permittivity was obtained for Bax Sr0.97−x Sm0.02 TiO3 ceramics sintered in nitrogen especially for x=0.2, which exhibited a weak temperature- and frequency- dependent giant permittivity (>10 4 ) as well as a low dielectric loss (mostly <0.05) over a broad temperature range from 20 to 300 °C. Based on the relaxation behaviors, XPS Spectrum and complex- impedance analysis of ceramics in different sintering atmosphere, the giant permittivity and low dielectric loss were due to the existence of the giant defect dipoles [Ti 4+ ·e - V o . . - e·Ti 4+ ] generated by the fully ionized oxygen vacancies and Ti 3+ ions, while the defect dipoles ( V Sr, , − V o . . ) and interfacial polarization caused the dielectric relaxation of the ceramics sintered in air or O2 .